2020
DOI: 10.26434/chemrxiv.11401347.v8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis and styrene copolymerization of novel dibromo and dichloro ring-disubstituted isobutyl phenylcyanoacrylates

Abstract: <p>Novel ring-disubstituted isobutyl phenylcyanoacrylates, RPhCH=C(CN)CO<sub>2</sub>CH<sub>2</sub>CH(CH<sub>3</sub>)<sub>2</sub> (where R is 2,5-dibromo, 3,5-dibromo, 2,3-dichloro, 2,4-dichloro, 2,5-dichloro, 2,6-dichloro, 3,4-dichloro, 3,5-dichloro) were synthesized by the piperidine catalyzed Knoevenagel condensation of ring-disubstituted benzaldehydes and isobutyl cyanoacetate and characterized by CHN analysis, IR, <sup>1</sup>H and <sup&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 18.1 and 35.9 mol% of MEPA is present in the copolymers prepared at ST/MEPA = 3 (mol), which is indicative of relatively high reactivity of the MEPA monomers towards ST radical which is typical of ring-substituted phenylcyanoacrylates [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Since MEPA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated MEPA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Mepa Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 18.1 and 35.9 mol% of MEPA is present in the copolymers prepared at ST/MEPA = 3 (mol), which is indicative of relatively high reactivity of the MEPA monomers towards ST radical which is typical of ring-substituted phenylcyanoacrylates [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Since MEPA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated MEPA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Mepa Copolymersmentioning
confidence: 99%
“…Earlier we have reported synthesis and styrene copolymerization a number of halogen ring-disubstituted PCAs, such esters as methyl [18][19][20][21], ethyl [22], propyl [23][24][25][26], isopropyl [27][28][29], butyl [30][31][32], and isobutyl [33][34][35].…”
mentioning
confidence: 99%
“…Thus, copolymerization of electrophylic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [16][17][18] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization of a number of dichloro and difluoro ringsubstituted methyl [19][20][21], ethyl [22], propyl [23][24][25], isopropyl [26,27], butyl [28,29], isobutyl [30,31], and 2-methoxyethyl [32] PCAs.…”
Section: Introductionmentioning
confidence: 99%